Zagadnienie upełnomocniania pracowników w koncepcji przywództwa personalistycznego i służebnego - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2010)
The paper presents concepts of personalistic leadership and servant leadership as an alternative to the technocratic management. The most important issue in the two concepts of leadership is the empowerment, that is, the capacity of building the staff (competence, knowledge, motivation). Servant leadership is an American concept of leadership very similar to the concept of personalistic leadership. The differences arise from how to give reasons – servant leadership has inspired by religion (Christianity), whereas the concept of personalistic leadership is based on the personalism and phenomenology.